Assessment of three types of intranasal nebulization devices in three‐dimensional printed models and volunteers: a pilot study. Issue 12 (20th July 2020) - Dong, Dong; Cai, Fangyu; Huang, Shuman; Zhu, Xiaoyuan; Geng, Jing; Liu, Jia; Lv, Lei; Zhang, Yanbing; Zhao, Yulin
Abstract : Background: Intranasal nebulization is an effective treatment for chronic rhinosinusitis and allergic rhinitis; however, terminal inhalation devices have not been fully studied. We compared the sinonasal aerosol distributions and adverse effects of different inhalation units. Methods: A mask, double‐head nozzle, and single‐head nozzle were applied to atomize the methylene blue solution to 3‐dimensional printed models of the pediatric nasal cavity, adult nasal cavity with septal deviation, and postsurgical paranasal sinuses, and staining of the different sites was scored. Volunteers received nebulization of normal saline via different devices; thereafter, the adverse effects were assessed using the visual analogue scale (VAS). Results: After nebulization, the staining scores for the middle turbinate and middle meatus of the pediatric and adult nasal cavity models and the score for the anterior ethmoid sinus of the sinus model with the single‐head nozzle were significantly higher than those with the mask and double‐head nozzle (all p < 0.05; η 2 for effect size estimates were above 0.68). Among the 31 volunteers, the adverse effects, including nasal irritation, facial pressure/pain, ear fullness/pain, postnasal drip, and throat irritation/cough, were mild. The variations in the incidence and VAS scores of the adverse effects among the devices were not significant (all p > 0.05). Conclusion: The single‐head nozzle was the most effective device in aerosol delivery to the lateral wall of the nasal cavity and sinuses; conversely, the mask yielded limited sinonasal deposition. Intranasal nebulization was well tolerated, and the adverse effects among the devices were comparable. These findings are meaningful for selecting and developing inhalation units.